2018
DOI: 10.1021/acsomega.8b00336
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Transfer Knowledge Graph among Amino Acids Derived from High-Throughput Electronic Structure Calculations for Protein Database

Abstract: The charge-transfer coupling is an important component in tight-binding methods. Because of the highly complex chemical structure of biomolecules, the anisotropic feature of charge-transfer couplings in realistic proteins cannot be ignored. In this work, we have performed the first large-scale quantitative assessment of charge-transfer preference by calculating the charge-transfer couplings in all 20 × 20 possible amino acid side-chain combinations, which are extracted from available high-quality structures of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Moreover, the significant enhancement in the E pa peak of the thiocholine may be due to fast electron transfer through the composite layers. In AChE-modified electrodes, a lower current response was observed ( Figure 4 b), assumed to be a result of slow electron transfer through BSA layers due to a low content of amino-acid-containing phenol backbones (e.g., tyrosine) [ 57 , 58 ]. Previous studies [ 32 , 59 , 60 , 61 ] have demonstrated that multiwall CNTs efficiently promote the electrocatalytic oxidation of thiocholine.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the significant enhancement in the E pa peak of the thiocholine may be due to fast electron transfer through the composite layers. In AChE-modified electrodes, a lower current response was observed ( Figure 4 b), assumed to be a result of slow electron transfer through BSA layers due to a low content of amino-acid-containing phenol backbones (e.g., tyrosine) [ 57 , 58 ]. Previous studies [ 32 , 59 , 60 , 61 ] have demonstrated that multiwall CNTs efficiently promote the electrocatalytic oxidation of thiocholine.…”
Section: Resultsmentioning
confidence: 99%
“…151 Currently several transferable ML potentials approaching the above goal are available, e.g., the ANI family of universal potentials. 136,148,168 Transferable ML models were also built for excitation energies, 169,170 intramolecular reorganization energies, 171 electron densities, 172,173 searching catalyst candidates, 174 pK a values, 175 charge-transfer couplings, 176 the density of electronic states, 177 band gaps, 178 and many other electronic properties (HOMO/LUMO gaps, polarizability, dipole moments, etc.). 161,162,179 It is also possible to use ML to predict several QC properties within the same framework.…”
Section: Is Emergingmentioning
confidence: 99%
“…This transformation has minor effects on the on-site energy and can be safely ignored if necessary. The TB parameters have been extensively studied for pure DNA complexes and protein complexes in the previous work (92,123).…”
Section: The Data Driven Tight Binding Model For Biomoleculesmentioning
confidence: 99%